Nano-to-microscale ductile-to-brittle transitions for edge cracking suppression in single-diamond grinding of lithium metasilicate/disilicate glass-ceramics. Issue 4 (April 2023) - Lu, Kuo; He, Quanpeng; Xie, Jin; Yang, Hao; Chen, Zhaojie; Ge, Dongsheng; Zhou, Cong; Yin, Ling
Abstract: To suppress grinding-induced edge cracks in dental lithium metasilicate/disilicate glass-ceramics (LMGC/LDGC), this paper established a contact stress model for single-diamond grinding (SDG) to relate their crack generation and ductile-to-brittle transition (DBT) thresholds with the mechanical properties, diamond tool profiles and process variables. Nanoindentation, friction test and SDG were conducted to unravel material responses and dynamic diamond grit-workpiece interactions to determine the DBT thresholds. The nanoindentation revealed significant indentation size effects (ISEs) on the hardness and elastic moduli of the ceramics. SDG clearly elucidated their DBT behaviors, wherein edge cracks initiated at diamond peripheries when the concurrent contact stresses reached the DBT thresholds. Accordingly, the indicated critical cutting depths for DBT may be changed from the nanoscale to the microscale by increasing the tool radius and reducing the machining speed. This research contributes to edge crack suppression for ductile machining of brittle materials at large removal rates. Graphical Abstract: ga1 Highlights: The contact stress model shows the property and tip-radius dependent DBT thresholds. Plastic deformation and significant ISE of LMGC and LDGC were observed in nanoindentation. Nanoscale edge crack initiated before bottom crack above critical contact stress in SDG. LDGC has a higher critical cutting depth for DBT than LMGC. Critical cutting depth for DBT may be changed from nanoscale to microscale with increased tool radius and reduced speed.